Interregional Inventor Mobility in the Russian Federation as Evidenced by European Patent Data - Jens K. Perret (Journal of the Knowledge Economy, 2021)
The transmission of knowledge between different entities is a central part of the concept of the national innovation system introduced by Lundvall. As knowledge in general, and tacit knowledge specifically, is a statistically rather intangible concept, alternative concepts need to be implemented to account for it.~This study uses the idea of inventor mobility to account for tacit knowledge transmissions across the regions of the Russian Federation. In particular, the combination of the results of both ideas is used to account for purely inventor-based knowledge flows. These flows are quantified, and it is shown that basic economic indicators like the quality of the regional research system and the regional income levels are suitable in describing the intensity of knowledge flows.
Keywords: O31; P25; R15; 330; Inventor mobility; Patent data; Russian Federation; Tacit knowledge; Spatial econometrics